2007
DOI: 10.1242/jcs.009159
|View full text |Cite
|
Sign up to set email alerts
|

Live imaging of chronic inflammation caused by mutation of zebrafish Hai1

Abstract: The hallmark of chronic inflammation is the infiltration and persistence of leukocytes within inflamed tissue. Here, we describe the first zebrafish chronic inflammation mutant identified in an insertional mutagenesis screen for mutants that exhibit abnormal tissue distribution of neutrophils. We identified a mutant line with an insertion in the Hepatocyte growth factor activator inhibitor 1 gene (hai1; also known as Spint1) that showed accumulation of neutrophils in the fin. The mutant embryos exhibited infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
145
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(159 citation statements)
references
References 54 publications
(71 reference statements)
12
145
0
Order By: Relevance
“…In view of this, we first addressed the expression of both zebrafish cxcl8 at different time points in 3 dpf Tg(mpx:gfp)i114 larvae under acute inflammatory conditions using quantitative PCR (qPCR). In this study, we made use of the tail fin transection model, a validated model to investigate acute inflammation (16)(17)(18)(19)(20)(21)(22)(23). We found that the mRNA levels of cxcl8-l1 and cxcl8-l2 were significantly increased in injured tail fin tissue and peaked at 1 hpw (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In view of this, we first addressed the expression of both zebrafish cxcl8 at different time points in 3 dpf Tg(mpx:gfp)i114 larvae under acute inflammatory conditions using quantitative PCR (qPCR). In this study, we made use of the tail fin transection model, a validated model to investigate acute inflammation (16)(17)(18)(19)(20)(21)(22)(23). We found that the mRNA levels of cxcl8-l1 and cxcl8-l2 were significantly increased in injured tail fin tissue and peaked at 1 hpw (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Additionally, the optical transparency of zebrafish and the development of fluorescent cell-specific transgenic lines have enabled the in vivo study of leukocyte biology (14,15). Zebrafish neutrophils have now been extensively studied in inflammation (16)(17)(18)(19)(20)(21)(22)(23), infection (24)(25)(26)(27), and tumor progression (28)(29)(30).…”
mentioning
confidence: 99%
“…32 The deletion of Hai-1/Spint1 in zebrafish resulted in disrupted epidermal integrity, susceptibility to apoptosis in keratinocytes, and inflammation. 32,33 Importantly, the epidermal phenotype of Hai-1/Spint1-deleted zebrafish was rescued by knockdown of matriptase. 32 The significant hyperkeratinization of the epidermis observed in B6Hai-1 ÏȘ/ÏȘHigh mice is reminiscent of ichthyosis.…”
Section: Discussionmentioning
confidence: 99%
“…41 In Hai-1/Spint1-deleted zebrafish, epidermal hyperproliferation occurs in later periods. 32,33 Taken altogether, disturbance of the balance of Hai-1/Spint1 and its cognate proteinase, such as matriptase, leads to deranged intracellular signaling and a proliferative skin disease. In this regard, Hai-1/Spint1 may be a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that matriptase is not co-expressed with HAI-1 in certain cell types and cultured cells (e.g., in ovary granulosa cells and in human monocyte THP-1 cells) (Szabo et al 2008;Kilpatrick et al 2006). In addition, genetic studies using zebrafish indicated that matriptase does not require HAI-1 for biological activity (i.e., for extracellular occurrence) (Carney et al 2007;Mathias et al 2007). When HAI-1 is not co-expressed, HAI-2 (also known as bikunin) and the other serine protease inhibitors could prevent intracellular self-degradation of matriptase (Szabo et al 2008).…”
Section: Discussionmentioning
confidence: 99%